2016
DOI: 10.3389/fpls.2016.01291
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Flavonoids in Novel Banana Germplasm during Fruit Development

Abstract: Banana is a commercially important fruit, but its flavonoid composition and characteristics has not been well studied in detail. In the present study, the metabolism of flavonoids was investigated in banana pulp during the entire developmental period of fruit. ‘Xiangfen 1,’ a novel flavonoid-rich banana germplasm, was studied with ‘Brazil’ serving as a control. In both varieties, flavonoids were found to exist mainly in free soluble form and quercetin was the predominant flavonoid. The most abundant free solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…have an upward trend (Zhao et al, 2012); the content of total flavonoids in the fruit of Musa nana Lour. variety ‘Brazil’ increased firstly and then decreased during fruit ripening (Dong et al, 2016); most flavonoid components such as quercetin and kaempferol increased during the development of yellow and black Brassica campestris L. seeds (Jiang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…have an upward trend (Zhao et al, 2012); the content of total flavonoids in the fruit of Musa nana Lour. variety ‘Brazil’ increased firstly and then decreased during fruit ripening (Dong et al, 2016); most flavonoid components such as quercetin and kaempferol increased during the development of yellow and black Brassica campestris L. seeds (Jiang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of total phenolic content as free and bound forms in Saba banana revealed that, between the two, a major fraction was contributed from bound phenolics. A previous evaluation of banana pulp showed that it contained significant levels of cell wall bound phenolics such as anthocyanidins 7 , quercetin, and cyanidin-3-O-glucoside chloride 24 . Since bound phenolics are bound to insoluble macromolecules, they have different pathways and absorption mechanisms in the gastrointestinal tract when compared to that of free phenolics.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of flavonoids helps to protect against cardiovascular disease [ 10 ]. Flavonoids exhibit a wide range of biological activities including strong antioxidant capacity, anti-inflammatory, anti-neoplastic, and hepatoprotective activity as well as vasodilatory actions [ 10 , 11 , 12 , 13 ]. Flavonols such as quercetin and kaempferol have the most potent effect on cardiovascular protection [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonols such as quercetin and kaempferol have the most potent effect on cardiovascular protection [ 14 , 15 ]. Various phenolic acids and flavonoids have been identified in bananas including ferulic, gallic, p-hydroxybenzoic, vanillic and syringic acids, p-coumaric acids, ellagic acid, catechin, epicatechin, quercetin, tannins, rutin and gallocatechin [ 3 , 11 ]. Kanazawa and Sakakibara [ 16 ] found dopamine (L-3,4-dihydroxyphenylalanine) levels ranging from 2.5–10 mg/100 g in banana pulp.…”
Section: Introductionmentioning
confidence: 99%